Effets potentiels du covid-19 sur l’activité touristique dans les pays membres de l’Organisation des États de la Caraïbe orientale et détermination du seuil optimal de recettes touristiques qui maximise leur croissance économique - Louis Dupont (Études Caribéennes)
The purpose of this paper is (i) to evaluate by using a model of standard regression, the potential effects of COVID-19 on tourism in countries of Organization of Eastern Caribbean States (OECS); (ii) to determine by using Hansen’s Threshold Auto Regressive model (TAR), the optimal size of tourism receipts that maximize the economic growth in this zone. In the first model, the paper finds that on account of the pandemic, the GDP of OECS’s countries could be reduced of 11.8% in 2020. In the second model, our empirical results show strong evidence of a non-linear relation between economic growth and tourism in two regimes. The regime with the degree of tourism specialization less than or equal to 25.27% (regime 1) and the regime with the degree of tourism specialization between 12.97% and 25.27% (regime 2). The optimal threshold is 25.27%. Its marginal effect is 0.17 point, “all things being equal to the otherwise”.